2014
DOI: 10.1002/jccs.201400158
|View full text |Cite
|
Sign up to set email alerts
|

Mode Specificity, Bond Selectivity, and Product Energy Disposal in X + CH4/CHD3 (X=H, F, O(3P), Cl, and OH) Hydrogen Abstraction Reactions: Perspective from Sudden Vector Projection Model

Abstract: Reactions between methane and various radicals have become the workhorse in our understanding of mode specificity and bond selectivity in bimolecular reactions. In this work, the recently proposed Sudden Vector Projection (SVP) model is used to gain insight into the existing experimental and theoretical data on these reactions. The SVP model attributes mode specificity and bond selectivity to the coupling of reactant modes/bonds with the reaction coordinate at the transition state. In the sudden limit, the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 121 publications
(80 reference statements)
3
32
1
Order By: Relevance
“…This is consistent with the sudden vector projection (SVP) model, which suggests a strong coupling between the C-H stretching (v 1 ) mode of CHD 3 and the reaction coordinate at the transition state. 76 On the other hand, the SVP model predicts no enhancement for rotational excitation of CHD 3 , as the rotational motions are poorly coupled with the reaction coordinate at the transition state. 76 However, Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is consistent with the sudden vector projection (SVP) model, which suggests a strong coupling between the C-H stretching (v 1 ) mode of CHD 3 and the reaction coordinate at the transition state. 76 On the other hand, the SVP model predicts no enhancement for rotational excitation of CHD 3 , as the rotational motions are poorly coupled with the reaction coordinate at the transition state. 76 However, Fig.…”
Section: Resultsmentioning
confidence: 98%
“…76 On the other hand, the SVP model predicts no enhancement for rotational excitation of CHD 3 , as the rotational motions are poorly coupled with the reaction coordinate at the transition state. 76 However, Fig. 3(a) clearly shows that the reactivity is different from different initial rotational states.…”
Section: Resultsmentioning
confidence: 98%
“…Nonetheless, it is convenient to plot the alignment of both reactant and product vectors with the RC vector, as done in Figure 2 for the Cl + CH 4 → CH 3 + HCl reaction. 47 Here, it is shown that the two stretching modes of CH 4 (ν 1 and ν 3 ) are best aligned with Q ⃗ RC , while the bending (ν 2 and ν 4 ) and translational (t) modes are less well aligned. Indeed, it is not difficult to visualize the large components of the two stretching modes in the RC vector as shown in Figure 2.…”
mentioning
confidence: 93%
“…54 While the SVP model has been generally successful in this respect, 55 including the X + CH 4 /CHD 3 reactions, 56 it fails to predict the observed vibrational enhancement in the title reaction. As shown in Table II, the projection of the CH (v 1 ) mode is merely 0.08 on the PWEM-SO PES, which is very close to that on the CSBB 56 suggesting very weak coupling with the reaction coordinate at the transition state, and thus small enhancement. The most likely reason for this failure is that the sudden model on which the SVP model is based does not hold in this system, due to the strong stereodynamic forces in the entrance channel and the low barrier.…”
mentioning
confidence: 99%